State Encroachment of Human Self: A Case Study of Citizenship - Subedi, Tek Nath (Interdisciplinary Journal of Management and Social Sciences, 2023)
State is the most powerful of all social institutions. It is supposed to enforce law and order in its territory, and ensure equality, liberty and fraternity in society. It provides citizenship certificate to its people by which an individual becomes a formal citizen of a nation. The citizenship certificate is often equated with national identity, which grants people certain rights and privileges. One can choose a partner, cast a vote, start a job, take the bank-loan, run a business, get into the share-market, or travel around the world alone only after receiving the maturity-license. In other words, the obtaining of a citizenship certificate bestows a person with a sense of triumph and liberation. Looking at the increased mobility of people from one place to another after being dissatisfied with the previous state of ‘citizenship’ and being fond of achieving a new type of ‘citizenship’ indicates that the citizenship certificate fosters the human self. Besides, citizenship has a responsibility side, which expects huge responsibility from the citizens. The responsibility-side seems as if it has dived deep into the human-self, terrorized the individual subjectivity and socialized the citizens to be highly submissive to it. Looking at the gap between the opportunity- and threat-side of the citizenship debate, this article attempts to examine whether the citizenship certificate liberates human subjectivity. It comes with a conclusion that the customary provision of a citizenship is more to offend than liberate the human self.